Collateral pledgeability and asset manager portfolio choices during redemption waves - Thiago Fauvrelle; Max Riedel; Mathias Skrutkowski (Leibniz Institute for Financial Research SAFE, 2024)
This paper studies whether Eurosystem collateral eligibility played a role in the portfolio choices of euro area asset managers during the "dash-for-cash" episode of 2020. We find that asset managers reduced their allocation to ECB-eligible corporate bonds, selling them in order to finance redemptions, while simultaneously increasing their cash holdings. These findings add nuance to previous studies of liquidity strains and price dislocations in the corporate bond market during the onset of the Covid-19 pandemic, indicating a greater willingness of dealers to increase their inventories of corporate bonds pledgeable with the ECB. Analysing the price impact of these portfolio choices, we also find evidence pointing to price pressure for both ECB-eligible and ineligible corporate bonds. Bonds that were held to a larger extent by investment funds in our sample experienced higher price pressure, although the impact was lower for ECB-eligible bonds. We also discuss broader implications for the related policy debate about how central banks could mitigate similar types of liquidity shocks.
Keywords: G11; G23; 330; Investment funds; dash-for-cash; corporate bonds; Eurosystem collateral eligibility